Unique Case of a Large Indolent Medullary Thyroid Carcinoma: Time to Reconsider the Medullary Thyroid Adenoma Entity?. Issue 2 (6th April 2019) - Censi, Simona; Cavedon, Elisabetta; Watutantrige-Fernando, Sara; Barollo, Susi; Bertazza, Loris; Manso, Jacopo; Iacobone, Maurizio; Nacamulli, Davide; Galuppini, Francesca; Pennelli, Gianmaria; Mian, Caterina
Abstract : Background: Medullary thyroid carcinoma (MTC) is a rare neuroendocrine cancer originating from parafollicular, calcitonin (Ctn)-producing C-cells. Prognosis correlates with primary tumor stage and Ctn levels. Patient: We describe a case of MTC involving a mass 7 cm in its largest dimension, associated with high Ctn concentrations (> 5, 000 pg/mL), but normal carcinoembryonic antigen levels, and with no lymph nodes or distant metastases, in complete remission after thyroid surgery. The MTC had very peculiar histological features, with an expansive, noninfiltrating growth around the thyroid follicles, and no signs of invasion. These histopathological characteristics are reminiscent of the C-cell adenoma described in animals. The tumor also revealed an ossifying extracellular matrix unlike the classical amyloid. Despite the size of the tumor and the patient's high Ctn levels at diagnosis, the case described here reached complete remission after surgery. Conclusions: Further studies are needed to clarify the characteristics of MTC and better predict its behavior at diagnosis.